Association between weight variability, weight change and clinical outcomes in hypertension - Richard Kazibwe; Matthew J. Singleton; Muhammad Imtiaz Ahmad; Arnaud D. Kaze; Parag A. Chevli; Juliana H. Namutebi; Ramla N. Kasozi; Denis D. Asiimwe; Joseph Kazibwe; Michael D. Shapiro; Joseph Yeboah (Elsevier, 2023)
Objective: The effect of body weight variability (BWV) and body weight change (BWC) in high-risk individuals with hypertension, but without diabetes mellitus (DM) remains unclear. We examined the effect of BWV and BWC on the primary outcome [the composite of myocardial infarction (MI), other acute coronary syndromes, stroke, acute decompensated heart failure (HF), or cardiovascular (CV) death] and all-cause mortality in the Systolic Blood Pressure Intervention Trial (SPRINT). Methods: In this post-hoc analysis, we used multivariate Cox regression models to examine the risk associated with BWV and BWC for the primary outcome in SPRINT. BWV was defined as the intra-individual average successive variability (ASV). BWC was defined as baseline weight minus final weight. Results: A total of 8714 SPRINT participants (mean age 67.8 ± 9.4 years, 35.1 % women, 58.9 % Whites) with available data on body weight were included. The median follow-up was about 3.9 years (IQR, 3.3-4.4). In multivariable-adjusted Cox models, each 1 unit standard deviation (SD) of BWV was significantly associated with a higher risk for the primary outcome, all-cause mortality, HF, MI, and stroke [HR(95 % CI)]: 1.13 (1.07-1.19; p < 0.0001), 1.22 (1.14-1.30; p < 0.0001), 1.16 (1.07-1.26; p < 0.001), 1.10 (1.00-1.20; p = 0.047), and 1.15 (1.05-1.27; p = 0.005), respectively. Similarly, each 1 unit SD of BWC was significantly associated with a higher risk of the primary outcome, all-cause mortality, MI, and HF: 1.11(1.02-1.21; p = 0.017), 1.44 (1.26-1.65; p < 0.0001), 1.16 (1.01-1.32; p = 0.041) and 1.19 (1.02-1.40; p = 0.031) respectively. However, there was no significant association with CV death (for both BWV and BWC) or stroke (BWC). Conclusion: In high-risk hypertension, BWV and BWC were both associated with higher risk of the primary outcome and all-cause mortality. These results further stress the clinical importance of sustained weight loss and minimizing fluctuations in weight in hypertension.